UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN METODE SQ3R PADA SISWA SMP - Desriana Hastuti; Martono Martono; Syambasril Syambasril (Universitas Tanjungpura, 2019)
Abstract This Research was based on the application of Curriculum 2013 which wasrelatively new in SMP Negeri 3 Suti Semarang. The aim of this research was toimprove students’ reading comprehension by using SQ3R method. DescriptiveQualitative was the method used in this research. The Result of this researchfound out that 1) Lesson plan that had been constructed by the teacher was wellprepared, appropriate and meets the criteria of lesson plan formulation in thecurriculum 2013. 2) Teaching learning process had been fulfilled the componentsbased on the curriculum 2013 by using scientific approach within discoverylearning model from preliminary activity, main activity and closing activity.3)Assessment and evaluation in the learning process of reading comprehension tofind the elements from fiction and nonfiction books were done well. Those threeaspects were measured by using four level values which were very good, good,sufficient and deficient. The conclusions in this research were planning,implementation, and assessment of the lesson plan which were the main problems in this research had been already good because they have fulfilled the main components of Permendikbud No 22 Tahun 2016 which was the basis of this research assessment, although there were still several aspects that need to be improved.Keywords: Improving, Reading Comprehension, SQ3R.